Reformulating Land Deed Officials Liability in Tax Document Forgery Cases - Teguh Adhipradana (Universitas Islam Sultan Agung, 2026)
This study aims to analyze the legal arrangements regarding the responsibilities of Land Deed Making Officials (PPAT) in the case of falsification of tax documents and formulate fair liability limits. This research uses normative juridical methods with laws and regulations, conceptual, and case approaches. The novelty of this research lies in the introduction of the concept of